Deteksi Dini dan Edukasi Pencegahan Stunting melalui Posyandu dan Kelas Ibu Balita di RA Madania Joho Pace Nganjuk - Guntur H., Bhaswarendra; Sona, Muklas Ary; Yuli Dianto, Alfin (Universitas Pangeran Diponegoro Nganjuk, 2025)
The integrated early stunting detection and education program at RA Madania Joho Pace combines Posyandu services and Mother-Toddler Classes to identify and address at-risk children. Key activities include monthly anthropometric screenings (weight/height, mid-upper arm circumference) conducted by trained teachers, followed by spiritually contextualized nutrition education for mothers. Measurement data is digitally shared with Posyandu for risk mapping, while collaborative nutrition sessions (teachers-cadres-nutritionists) teach the use of local nutrient-rich foods like eggs and fish. This integration model achieved an 8% reduction in stunting-risk cases and a 25% increase in maternal knowledge. Primary challenges were low father participation (15%) and limited measurement tools. The program demonstrates school-Posyandu collaboration as an effective stunting prevention strategy for rural Indonesia.